Cloning and expression in Escherichia coli of the cDNA for murine tumor necrosis factor. - Pennica, D (1985)
A murine tumor necrosis factor (MuTNF) cDNA was isolated from a cDNA library prepared by using mRNA from the murine macrophage-like cell line PU5-1.8 induced with 4 beta-phorbol 12 beta-myristate 13 alpha-acetate. The cDNA encodes a polypeptide consisting of a 79 amino acid pre sequence followed by a mature MuTNF sequence of 156 amino acids. The 235 amino acid murine pre-TNF polypeptide is 79% homologous to the human pre-TNF protein. There is one potential N-linked glycosylation site on MuTNF, in contrast to human TNF, which lacks any such site. The MuTNF cDNA, when engineered for expression in Escherichia coli, was found to direct the synthesis of biologically active MuTNF as determined by its cytotoxicity against several transformed cell lines.